2019
DOI: 10.1212/wnl.0000000000007326
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive period and risk of dementia in a diverse cohort of health care members

Abstract: ObjectiveWomen have >50% greater lifetime risk of dementia than men but the role of female-specific endocrine milieu is not well-understood. This study evaluates associations between indicators of estrogen exposure from women's reproductive period and dementia risk in a large diverse population.MethodsWe evaluated 15,754 female members (29.9% nonwhite) of Kaiser Permanente with clinical examinations and health survey data from 1964 to 1973 and were members as of January 1, 1996. In midlife (mean age 51.1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
101
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(119 citation statements)
references
References 31 publications
8
101
1
Order By: Relevance
“…[47], cumulative numbers of gestations were found to reduce the risk of incident AD. Further supporting a link between reproductive life and dementia risk, higher age at menarche, menopause before age 47 and shorter reproductive span were shown to increase the risk of incident dementia in a large prospective cohort study with 15 754 participants [48]. These results need to be confirmed in further studies.…”
Section: Risk Factors and Preventionmentioning
confidence: 94%
“…[47], cumulative numbers of gestations were found to reduce the risk of incident AD. Further supporting a link between reproductive life and dementia risk, higher age at menarche, menopause before age 47 and shorter reproductive span were shown to increase the risk of incident dementia in a large prospective cohort study with 15 754 participants [48]. These results need to be confirmed in further studies.…”
Section: Risk Factors and Preventionmentioning
confidence: 94%
“…The Women's Health Initiative Memory Study reported that women assigned exogenous estrogens had an increased risk of dementia, 6 while others reported no associations 7,8 . The effect of long‐term endogenous estrogen exposures on dementia risk and Alzheimer's disease (AD) is less clear 9‐11 . There are different forms of endogenous estrogens.…”
Section: Introductionmentioning
confidence: 99%
“…The Rotterdam Study, which included women with natural menopause, reported that those with longer reproductive period had higher risk of dementia and AD, especially among apolipoprotein E ( APOE ) ε4 carriers. 9 In contrast, the Kaiser Permanente Study (KP) reported a higher risk of dementia in those with shorter reproductive span, 11 while the 10/66 study found no association between reproductive period and dementia incidence 10 . None of the studies included information on oral contraceptives, 9‐11 and the two latter did not assess HRT exposure 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, female-specific hormonal transitions including puberty, parity and menopause can help in our understanding of why women are more likely to be diagnosed with AD (see Table 2). Earlier onset of menopause, either surgical (ovarian removal) or spontaneous (gradual cessation of menses at ~51yrs), is associated with increased AD/dementia risk (Bove et al, 2014;Fox et al, 2013a;Gilsanz et al, 2019;Rocca et al, 2007). Total reproductive years (age at menarche to age at menopause) has repeatedly been shown to be negatively correlated with the rate of AD diagnosis, indicating that duration of ovarian hormone exposure protects against AD (Fox et al, 2013a;Gilsanz et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier onset of menopause, either surgical (ovarian removal) or spontaneous (gradual cessation of menses at ~51yrs), is associated with increased AD/dementia risk (Bove et al, 2014;Fox et al, 2013a;Gilsanz et al, 2019;Rocca et al, 2007). Total reproductive years (age at menarche to age at menopause) has repeatedly been shown to be negatively correlated with the rate of AD diagnosis, indicating that duration of ovarian hormone exposure protects against AD (Fox et al, 2013a;Gilsanz et al, 2019). In fact, there is evidence that the 17-estradiol (E2) decline at menopause may contribute to cognitive decline in women at late midlife, and that estrogen replacement initiated shortly after menopause reduces the incidence of AD (Kawas et al, 1997;Merlo et al, 2017;Shao et al, 2012;Tang et al, 1996;Whitmer et al, 2011).…”
Section: Introductionmentioning
confidence: 99%